Application of FTA and SPAR-H Method to Control Work Accident at PG. Krebet Baru - Wijaya, Yedija Prasetya; Noya, Sunday Alexander Theophilus (Jurnal Ilmiah Teknik Industri, 2016)
This research is conducted because a high number of accidents occured during the workplace in PG. Krebet Baru. There were about 45 accidentsin 2013 and 32 out of 45 accidentscame from the Maintenance Division. Â This research is needed for the purpose of decreasing the number of accidents. The methods used in this research are hierarchycal task analysis (HTA), standarized plant risk analysishuman reliability assessment (SPAR-H), and fault tree analysis (FTA). In this research, there are 4 stations. They are milling station, purification, maturation, and spinning. Based on this research, there are 5 accidents. They are damaged muscle, damaged bone, graze, damaged eye, and injuries from a fall. Based on this research, it can be concluded that the workplace conditions and the lack of worker awareness on the importance of protective equipment usage are the main causes of these work accidents. Based on these causes, the suitable solution is to change several work methods and instruct the workers about using protective equipment.